2022
DOI: 10.1126/scitranslmed.abj2829
|View full text |Cite
|
Sign up to set email alerts
|

MAIT and Vδ2 unconventional T cells are supported by a diverse intestinal microbiome and correlate with favorable patient outcome after allogeneic HCT

Abstract: Microbial diversity is associated with improved outcomes in recipients of allogeneic hematopoietic cell transplantation (allo-HCT), but the mechanism underlying this observation is unclear. In a cohort of 174 patients who underwent allo-HCT, we demonstrate that a diverse intestinal microbiome early after allo-HCT is associated with an increased number of innate-like mucosal-associated invariant T (MAIT) cells, which are in turn associated with improved overall survival and less acute graft-versus-host disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 83 publications
2
36
0
Order By: Relevance
“…A higher than median MAIT cell frequency at day 30 post-transplant was correlated with OS and decreased NRM. An association between MAIT frequency and lowered incidence of grades 2 to 4 aGVHD as well as GI GVHD was also seen ( 59 ). Prior to our study, Bhattacharyya et al ( 58 ) had observed that increases in absolute MAIT cell count (in increments as small as 10 MAIT cells/μL) in the blood in the early post-HCT period were associated with a reduced risk of GVHD in a cohort of 105 patients.…”
Section: Associations Between the Intestinal Microbiome Immune Recons...mentioning
confidence: 97%
See 4 more Smart Citations
“…A higher than median MAIT cell frequency at day 30 post-transplant was correlated with OS and decreased NRM. An association between MAIT frequency and lowered incidence of grades 2 to 4 aGVHD as well as GI GVHD was also seen ( 59 ). Prior to our study, Bhattacharyya et al ( 58 ) had observed that increases in absolute MAIT cell count (in increments as small as 10 MAIT cells/μL) in the blood in the early post-HCT period were associated with a reduced risk of GVHD in a cohort of 105 patients.…”
Section: Associations Between the Intestinal Microbiome Immune Recons...mentioning
confidence: 97%
“…In humans, MAIT cells represent up to 10% of all circulating CD3+ T cells ( 3 ). In the setting of clinical allo-HCT, frequency of donor graft-derived MAIT cells in the early post-HCT period has been linked with favorable transplant outcomes in a number of studies ( 58 , 59 ). We have recently reported a relationship between MAIT cells and transplant outcome, in a cohort of 118 PBSC graft recipients ( 59 ).…”
Section: Associations Between the Intestinal Microbiome Immune Recons...mentioning
confidence: 99%
See 3 more Smart Citations